2018
DOI: 10.3390/met8040282
|View full text |Cite
|
Sign up to set email alerts
|

Skeletonization, Geometrical Analysis, and Finite Element Modeling of Nanoporous Gold Based on 3D Tomography Data

Abstract: Abstract:Various modeling approaches simplify and parametrize the complex network structure of nanoporous gold (NPG) for studying the structure-property relationship based on artificially generated structures. This paper presents a computational efficient and versatile finite element method (FEM) beam model that is based on skeletonization and diameter information derived from the original 3D focused ion beam-scanning electron microscope (FIB-SEM) tomography data of NPG. The geometrical skeleton network is tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(76 citation statements)
references
References 42 publications
4
71
1
Order By: Relevance
“…By this approach, common issues with determining the percolation threshold p c and exponent could be avoided. For measuring the total cut fraction of a real structure, e.g., from a skeleton of a FIB tomography (Hu et al, 2016;Ziehmer et al, 2016;Hu, 2017;Richert and Huber, 2018), the related fully connected reference is required; however, this is unknown. Alternatively, the average coordination number z of a 3D network could be measured, because it is connected with the total cut fraction by the linear relationship, as given in Equation (12).…”
Section: Relationship Between Scaled Genus Density and Average Coordimentioning
confidence: 99%
See 1 more Smart Citation
“…By this approach, common issues with determining the percolation threshold p c and exponent could be avoided. For measuring the total cut fraction of a real structure, e.g., from a skeleton of a FIB tomography (Hu et al, 2016;Ziehmer et al, 2016;Hu, 2017;Richert and Huber, 2018), the related fully connected reference is required; however, this is unknown. Alternatively, the average coordination number z of a 3D network could be measured, because it is connected with the total cut fraction by the linear relationship, as given in Equation (12).…”
Section: Relationship Between Scaled Genus Density and Average Coordimentioning
confidence: 99%
“…The first FEM models built from 3D FIB tomography data were presented independently by Hu et al (2016) and Mangipudi et al (2016). The model of Hu et al (2016) has been further refined by Richert and Huber (2018), who analyzed the detected ligament shapes and investigated the predictive capability of the FEM beam model in comparison to the 3D solid model of Hu et al (2016). Soyarslan et al (2018) used complex artificially generated structures and FEM solid modeling for validating an analytical solution that relates the solid fraction to the scaled genus density.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is commonly used to estimate the mean trabecular thickness of trabecular bone (Day et al, 2000;Almhdie-Imjabber et al, 2014), or other bone structures (Witkowska et al, 2014), because it is a powerful and fast volume-based algorithm. In the context of NPG the Thickness algorithm has been applied for analyzing 3D tomography data or voxel models by Hu et al (2016), Mangipudi et al (2016), Richert and Huber (2018), and Soyarslan et al (2018a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, for the prediction of mechanical properties using FEM, the correct diameter distribution along the ligament axis is crucial. Richert and Huber (2018) showed that the Thickness algorithm reaches its limits when being applied to typical shapes of NPG ligaments, due to the strongly varying diameter along the ligament axis. The resulting overestimation in ligament radius up to 30% has a strong impact on the predicted mechanical stiffness, which can deviate by a factor of more than two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation